Investigations of milk-fat lamb production practices for western Kansas - Menzies, C.; Banburry, E. (Kansas Agricultural Experiment Station, 2011)
This sheep project was initiated in the spring of 1959 as a new research project at the Colby Branch Experiment Station in cooperation with the Department of Animal Husbandry, Kansas State University. One hundred fifty-one finewool yearling ewes were purchased from near Del Rio, Texas, May 4, 1959. An additional 200 similar yearling ewes were purchased from the same area May 13, 1960. These ewes are handled in a typical Kansas early lambing program. The ewes are bred to purebred Hampshire rams and all lambs are sold in the spring as milk-fat lambs. Over-all objectives of this project are to determine the productive and economic value of various management practices, types of pastures, feeds, feed additives, and combinations of these to maintain a commercial ewe flock and to produce milk-fat lambs for a spring market under western Kansas conditions.
Keywords: Sheep; Productive value; Economic value; Milk-fat lambs